Legal issues of mobile apps a practical guide - Iglezakis, Ioannis, 1965- (Kluwer Law International B.V., 2020)
In less than ten years touchscreen smartphones and their apps have created an unprecedented technological revolution. Yet they are rife with serious potential for breaches of privacy and security, and a lack of uniform rules makes navigation of the legal landscape extremely difficult. Addressing this unstable regulatory environment, this concise, practical guide for the first time provides a measure of legal certainty. It examines case law and legislation in Europe and the United States to highlight the rights and obligations of all actors involved in the marketing of mobile apps, bring to light essential principles and recommend some viable solutions.